In vitro and in vivo Human Metabolism of (S)-[18F]Fluspidine – A Radioligand for Imaging σ1 Receptors With Positron Emission Tomography (PET) - Ludwig, Friedrich-Alexander; Fischer, Steffen; Houska, Richard; Hoepping, Alexander; Deuther-Conrad, Winnie; Schepmann, Dirk; Patt, Marianne; Meyer, Philipp M.; Hesse, Swen; Becker, Georg-Alexander; Zientek, Franziska Ruth; Steinbach, Jörg; et al. (Frontiers in Pharmacology, 2019)
(S)-[18F]fluspidine ((S)-[18F]1) has recently been explored for PET imaging of sigma-1 receptors in humans. In the current report, we have used plasma samples of healthy volunteers to investigate the radiometabolites of (S)-[18F]1 and elucidate their structures with LC-MS/MS. For the latter purpose additional in vitro studies were conducted by incubation of (S)-[18F]1 and (S)-1 with human liver microsomes (HLM). In vitro metabolites were characterized by interpretation of MS/MS fragmentation patterns from collision-induced dissociation or by use of reference compounds. Thereby, structures of corresponding radio-HPLC-detected radiometabolites, both in vitro and in vivo (human), could be identified. By incubation with HLM, mainly debenzylation and hydroxylation occurred, beside further mono- and di-oxygenations. The product hydroxylated at the fluoroethyl side chain was glucuronidated. Plasma samples (10, 20, 30 min p.i., n=5-6), obtained from human subjects receiving 250-300 MBq (S)-[18F]1 showed 97.2%, 95.4%, and 91.0% of unchanged radioligand, respectively. In urine samples (90 min p.i.) the fraction of unchanged radioligand was only 2.6% and three major radiometabolites were detected. The one with the highest percentage, also found in plasma, matched the glucuronide formed in vitro. Only a small amount of debenzylated metabolite was detected. In conclusion, our metabolic study, in particular the high fractions of unchanged radioligand in plasma, confirms the suitability of (S)-[18F]1 as PET radioligand for sigma-1 receptor imaging.